PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) DALAM MENGENTASKAN KEMISKINAN DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2018 - Azizah, Fitria Nur; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Family of Hope Program (PKH) is a conditional social assistance program for poor and vulnerable families and / or individuals who are registered in the integrated data handling program for the poor, processed by data centers and social welfare information and designated as PKH beneficiary families. The Family of Hope Program (PKH) has a goal which is to reduce poverty and inequality in Pekanbaru City. Tenayan Raya sub-district is the sub-district that has the highest number of PKH beneficiary families in Pekanbaru City. This research was conducted at the Social Service City of Pekanbaru. The importance of the role of the Social Service in the implementation of PKH in Pekanbaru City is that in the implementation of PKH in the field in accordance with the objectives to be achieved by the Government.            The purpose of this study was to determine the implementation of the Family Hope Program (PKH) in Pekanbaru City especially in the District of Tenayan Raya as well as the factors that influence the implementation of the program.            The theoretical concepts used by the authors are Program Implementation Theory by David C. Korten and Poverty Theory. This type of research is a qualitative descriptive. Data collection techniques carried out through interviews with research informants selected purposively and document recording. Data analysis techniques in this study used qualitative data analysis methods.            The results of this study indicate that the implementation of the Family Hope Program (PKH) in alleviating poverty in the Tenayan Raya District of Pekanbaru City is still not optimal. Factors that influence the less optimal implementation of PKH in Tenayan Raya based on David C. Korten's theory are the program implementers, the small nominal amount of assistance, and program targets. Keywords: Implementation, Hope Family Program.